COLOR THERAPY: रंग चिकित्सा - Charate, Vandana (International Journal of Research -GRANTHAALAYAH, 2014)
Color is synonymous with various sensations and sensations in human life. The human world is also made up of diverse colors. That is why in Indian culture too, the nature of various rituals is embedded around colors. They provide excitement, despair, happiness and sorrow. In the same way, the body of man is also made of different colors, which is reflective of his mental and physical condition, this balance of colors is nature ie God. In this, a person becomes unwell due to disturbances or imbalances, then through various treatments or medical methods, efforts are made to balance these colors and make the human being healthy. This therapy comes under alternative medicine, which is called "cryotherapy". रंग मानवीय जीवन में विविध अनुभूतिय¨ं एवं संवेदनाअ¨ं का पर्याय है। मनुष्य की दुनिया भी विविध रंग¨ं से बनी है। इसीलिये भारतीय संस्कृति में भी विविध संस्कार¨ं का स्वरूप रंग¨ं क¢ इर्दगिर्द ही समाया हुआ है। ज¨ उत्साह, निराशा, सुख और दुख की अनुभूति करवाते हैं। इसी तरह मनुष्य का शरीर भी विविध रंग¨ं से निर्मित है, ज¨ उसकी मानसिक और शारीरिक स्थिति का द्य¨तक है, रंग¨ं का यह संतुलन प्रकृति अर्थात् ईश्वर प्रदŸा ह¨ता है। इसमें गडबडी या असंतुलन ह¨ने पर मनुष्य अस्वस्थ ह¨ जाता है, तब विविध उपचार या चिकित्सा पद्धति क¢ माध्यम से इन रंग¨ं क¨ संतुलित कर मनुष्य क¨ स्वस्थ बनाने का प्रयास किया जाता है। यह चिकित्सा वैकल्पिक चिकित्सा क¢ अन्तर्गत आती है, जिसे ‘‘क्र¨म¨थेरेपी (ब्ीतवउवजीमतंचल)’’ कहा जाता है।